The Development of “Emotion Faces” as a Visual Tool for Facilitating Emotion Regulation Among Primary School Students - Agnely Risqy Aulia; Yohana Wuri Satwika (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
motional difficulties among elementary school students often hinder learning processes and classroom interactions. Many students struggle to recognize, express, and regulate their emotions due to limited emotional vocabulary and inadequate coping mechanisms. This study aims to develop and implement a visual-based educational media called “Emotion Faces” to support emotional regulation in elementary school students. The research employed a descriptive qualitative method and was conducted at SDN Ketintang II/410 Surabaya during the implementation of the Kampus Mengajar Program. Data were collected through participatory observation, informal interviews, and documentation involving 30 students from grades IV and V, along with two classroom teachers. The results indicate that the use of “Emotion Faces” helped students better identify their emotions and express them through visual symbols such as facial drawings and color. Teachers also reported improved understanding of students’ emotional states and classroom climate. This study concludes that simple, low-cost, and creative media can be effective in fostering emotional literacy and regulation among young learners in the classroom setting.